Fabrication of a turbine disk alloy by electron beam sheet lamination and investigation on the improved high temperature creep performance. (20th April 2023) - You, Xiaogang; Tan, Yi; Takeyama, Masao; Li, Pengting; Li, Yi; Zhang, Huixing; Cui, Hongyang; Cui, Chuanyong; Wang, Yinong; Li, Jiayan; Zhang, Zhijun; Dong, Gengyi; et al.
Highlights: A turbine disk alloy was made by EBSL, giving refined microstructure and high purity. The EBSL alloy shows much better creep performance compared with the IM alloy. EBSL restrains the formation of large inter-dendritic carbides during solidification. In IM alloy, the large MC carbides result in alloy failure by particle fracturing. The γ′ and γ″ contribute to strengthening and coordinating intragranular deformation. Abstract: A turbine disk alloy was prepared by electron beam sheet lamination (EBSL), giving a refined microstructure and high purity, and the microstructure-property relationship of this alloy has been developed. The alloy showed an outstanding creep life of 1266.3 h at 953 K/500 MPa. Compared with the conventional vacuum induction melted and vacuum arc re-melted alloy, a smaller dendrite arm spacing of less than 23 µm was obtained through the EBSL method, which restricted the formation of large inter-dendritic carbides. As a result, the typical intergranular failure mode was observed in the EBSL alloy, whereas the transgranular fracture mode was dominant in the conventional alloy. The inter-dendritic MC carbides formed from the reverse diffusion of Nb are believed to either impede grain boundary sliding or initiate cracks, depending on their size and morphology. The tiny grain boundary precipitates of the δ phase in the EBSL alloy could reduce the critical stress for microvoid nucleation to 161.07 MPa by decohering the particle/matrix interface, or allowing vacancy condensation near the δ interface, resulting in the formation of grain boundary microcracks. In the conventional alloy, however, the larger-sized MC carbides which were formed during the solidification process (0.36 vol.%) nucleated the microcracks within the particles, leading to the transgranular fracture. Furthermore, the results indicated that the nanoscale γ′ and γ″ precipitates contributed primarily to strengthening and coordinating intragranular deformation during creep, in which the Orowan mechanism and shearing of a /6<211> partial dislocations and a /2<110> doublets were active for γ′ and γ″ precipitates, respectively.